Inequality Between The Potential of Fishery Resources and The Poverty Level of Fisherman Communities in Coastal Areas - Kurnia, Ida; Yuan Yuan, Luo (LAW REFORM, 2026)
Indonesia, recognized as a significant maritime nation, documented a capture fisheries output of 7.7 million tonnes in the year 2023, positioning it among the foremost producers globally. Notwithstanding its substantial economic prospects, the well-being of coastal fishing communities remains suboptimal, signifying an enduring disparity between the wealth derived from marine resources and the prevailing social conditions. This research endeavors to furnish a contemporary examination of this incongruity by exploring the divergence between Indonesia's fisheries potential and the impoverishment faced by fishermen. Employing a legal-empirical framework, this investigation scrutinizes pertinent policies and integrates interviews with fishers from the Pekalongan, Juwana, and Tegal locales. The findings indicate that numerous fishing households exist in vulnerable conditions attributable to inadequate fisheries governance, resource overexploitation, and limited access to essential infrastructure and services, including education and healthcare. The activities of economically and politically hegemonic entities exacerbate the marginalization of fishers, while bureaucratic inefficiencies and corruption at both local and national strata obstruct enhancements in welfare. These inequities hinder social and economic advancement, posing a threat of ecological degradation and jeopardizing the long-term sustainability of marine resources. The research posits that the resolution of these challenges necessitates comprehensive and coordinated strategies that amalgamate economic, social, and environmental objectives within the paradigm of coastal development.